2021
DOI: 10.1177/13540688211047768
|View full text |Cite
|
Sign up to set email alerts
|

Political donations and the gender gap during COVID-19

Abstract: What effect has the COVID-19 pandemic had on the political donations gender gap in Canada? Drawing on data from two national surveys conducted in May and August 2020, as well as Elections Canada data from 2019 and 2020, we find an overall decline in contributions to political parties and a reduced but still significant gender gap, with women less likely to donate to political parties than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Most of these larger normative differences were reflected to some extent when considering the observed preferences of donors within the sample (i.e., the causes participants had supported in the previous year). Beyond this study, identified normative causes also align with evidence that men are more likely to actually support sports charities (Piper & Schnepf, 2008) and political charities (McMahon et al, 2023;Showers et al, 2011), while women are more likely to actually support animal charities (Piper & Schnepf, 2008;Srnka et al, 2003). Social norms therefore may be the mechanism which explains why men and women are more or less likely to support these causes.…”
Section: Discussionsupporting
confidence: 69%
“…Most of these larger normative differences were reflected to some extent when considering the observed preferences of donors within the sample (i.e., the causes participants had supported in the previous year). Beyond this study, identified normative causes also align with evidence that men are more likely to actually support sports charities (Piper & Schnepf, 2008) and political charities (McMahon et al, 2023;Showers et al, 2011), while women are more likely to actually support animal charities (Piper & Schnepf, 2008;Srnka et al, 2003). Social norms therefore may be the mechanism which explains why men and women are more or less likely to support these causes.…”
Section: Discussionsupporting
confidence: 69%
“…We also include a variable for the gender of the leadership contestant. Many of the financial aspects of party politics have been found to be gendered, with donations to women candidates following an affinity pattern (Tolley et al 2022) and with women donating less in general (McMahon et al 2021). 14 If donors are motivated by affinity more than a connection with the party, those who supported a woman leadership candidate may be less likely to continue donating to the party afterwards.…”
Section: Data Methods and Casementioning
confidence: 99%